Status of SDG 6 and significance of PPPs in improved water infrastructure in Africa - Vyas-Doorgapersad, Shikha (Edelweiss Applied Science and Technology, 2025)
Water is a basic necessity of everyday life, however social and economic environments may cause discrimination regarding the use of water. The discrimination occurs in the form of geography whereby rural areas has less access to water; financial status of municipalities that struggle to upgrade water infrastructure and negatively impact the flow of water; and now a days technology whereby digital illetracy and technologically-deprived areas may encounter challenges regarding water usage, maintenance and control, and maintaining the water management system. This scanrio is explored in the African context, holistiocally, where institutional poverty can be a major cause of water deprivation in the sense of lack of technology, resources, capacity, technical skills and infrastructure that may hamper the effective implementation of water infrastructure-related processes and structures. The articles utilises qualitative research approach to gather information that is compiled through literature and document reviews, and thereafter assessed through conceptual analysis. The findings confirm that the continent, more or less, face the similar challenges of poverty, technological-deprivation, inadequate skills base in water resource management, capacity-building interventions to upgrade the expertise of government and municipal personnel equipping them to handle water governance, to state a few. The study suggests that governments in African States may consider to design and implement pro-poor strategies within their socio-economic-political contexts. This is important to provide water services to communities within their environment with a clear understanding of demographics. The study further recommends that public private partnerships (PPPs) can be a solution to improve the challenges related to water resource management. The rationale is that PPPs have institutional capacity and resources that governments may lack hence can work together for mutually beneficial mandate that is to provide better services, and in this case, effective water services to external customers (community members).